Explaining catch-up in human development: A political economy comparison of the Philippines and Viet Nam since 1986 - Baulch, Bob (Institute for Poverty Alleviation and International Development, 2019)
This paper examines the Philippines and Viet Nam’s contrasting human development and growth experiences since 1986 from a political economy perspective. By a sequenced combination of market liberalization, land reform, and public investments in health and education, plus large aid and foreign direct investment inflows, Viet Nam generated broad-based, sustained, and rapid economic growth. Viet Nam’s authoritarian but socially inclusive governments then used progressive taxation and inter-provincial transfers to translate this growth into human development outcomes. In contrast, in the Philippines, traditional elites were able to dominate the democratic process, capture rents and divert resources away from investment in human development and infrastructure, thereby stifling a short-lived growth acceleration. The Philippines was also caught in a low-revenue, low-expenditure trap due to its porous and regressive tax system and self-reinforcing internal revenue allotment mechanism. While not without difficulties in terms of rising vertical and horizontal inequalities, economic growth and human development in Viet Nam have therefore been more inclusive, as well as faster, than in the Philippines.